(untitled) (Al-Academy, 2025)
The material plays a pivotal role in installation art, serving as a creative medium that enables the artist to translate their contemporary artistic ideas into interactive artworks presented in specific spaces. The artist’s selection of the appropriate medium requires continuous practice and experimentation to ensure the achievement of formal and expressive values in the artwork, while enhancing direct interaction between the work and the audience. Thus, installation art becomes a fertile ground for creativity and artistic innovation when materials are employed consciously and creatively. The research problem revolves around exploring the role of materials as a primary creative medium in installation art, focusing on how contemporary artists choose suitable materials to achieve aesthetic, expressive, and symbolic dimensions. This research paper seeks to analyze the relationship between materials and the creative medium, and to explore the impact of this interaction on achieving artistic and aesthetic values, reflecting the artist’s ability to utilize materials to produce works that carry innovative philosophical meanings. This paper adopted a descriptive-analytical approach to study a collection of works by contemporary artists in the field of installation art by analyzing the role of materials in these works and their nature as a creative medium on one hand, and their role in achieving formal and expressive values on the other. The paper also examined the relationship between artistic and aesthetic values and the materials used in those works. The paper reached a set of conclusions, the most prominent of which are: the importance of the artist’s selection of appropriate materials in installation art, and how this process can achieve numerous artistic and aesthetic values. These values determine the artwork’s ability to evoke admiration and awe in the audience. Additionally, the possibilities and challenges of materials were explored in a collection of works by contemporary artists in installation art. It was also found that materials, as a creative medium, contribute to achieving high-quality formal and expressive values. These values focus on the visual structure of the work and the meanings it carries, i.e., how artistic elements are organized and what the work expresses, thereby enhancing the aesthetic and philosophical impact of the artwork